An Analysis on the Speech Act of Mark Zuckerberg in English Speeches YouTube Channel - Ruth Tania Caroline; Ultarina Sitorus; Bloner Sinurat; Herman; Dumaris E. Silalahi (Zien Journals, 2021)
The goal of this study was to identify different types of illocutionary behavior in Mark Zuckerberg's speech "Find Your Purpose." There are two main issues in the research: (1) What types of illocutionary acts does Mark Zuckerberg use in his YouTube speeches in English? In Mark Zuckerberg's YouTube videos, what kinds of illocutionary acts are you most likely to see? The researchers employed a method known as content analysis. According to Searle theory, there are five types of illocutionary acts: assertives, directives, expressives, compromises, and declarations. The researchers analyzed a script speech by Facebook founder Mark Zuckerberg entitled "Find Your Purpose." Data from Mark Zuckerberg's speeches revealed 35 instances of illocutionary behavior, according to the researchers. These five types of illocutionary acts can all be found in a speech: assertive statements; directive statements; expressive statements; communicative statements; and declaration statements. And based on the findings of this study, it's safe to say that the dominant style of illocutinary act in speech is intimate style, with assertives accounting for 40% of cases, directives for 43%, expressives for 8%, commisives for 6%, and declarations for 1% of cases (3 percent)
Keywords: Illocutionary Act; Pragmatics; Speech; English